ChemInform Abstract: An Efficient and Convenient Synthesis of N‐Substituted Amides under Heterogeneous Condition Using Al(HSO4)3 via Ritter Reaction. Issue 28 (23rd June 2016) - Karimian, Elnaz; Akhlaghinia, Batool; Ghodsinia, Sara S. E.
Abstract: Reactions between various aliphatic and aromatic nitriles and benzylic alcohols are catalyzed by Al(HSO4 )3 leading to the title N‐substituted amides (III) (20 examples) via the Ritter mechanism.